Cross-border cooperation in the Galicia-Northern Portugal euroregion - Ferreira, Vera (2019)
After centuries of mistrust and rivalry, territorial cooperation relations – and, specifically, cross-border cooperation – between Portugal and Spain are nowadays characterised by an increasing dynamism. Indeed, since the second half of the 1970s, we have watched a gradual evolution and consolidation of such relations.